Nuclear positioning in muscle development and disease - Folker, Eric; Baylies, Mary (Frontiers in Physiology, 2013)
Muscle disease as a group is characterized by muscle weakness, muscle loss, and impaired muscle function. Although the phenotype is the same, the underlying cellular pathologies, and the molecular causes of these pathologies, are diverse. One common feature of many muscle disorders is the mispositioning of myonuclei. In unaffected individuals myonuclei are spaced throughout the periphery of the muscle fiber such that the distance between nuclei is maximized. However, in diseased muscles, the nuclei are often clustered within the center of the muscle cell. Although this phenotype has been acknowledged for several decades, it is often ignored as a contributor to muscle weakness. Rather, these nuclei are taken only as a sign of muscle repair. Here we review the evidence that mispositioned myonuclei are not merely a symptom of muscle disease but also a cause. Additionally, we review the working models for how myonuclei move from two different perspectives, from that of the nucleus and from that of the cytoskeleton. We further compare and contrast these mechanisms with the mechanisms of nuclear movement in other cell types both to draw general themes for nuclear movement and to identify muscle-specific considerations. Finally, we focus on factors that can be linked to muscle disease and find that genes that regulate myonuclear movement and positioning have been linked to muscular dystrophy. Although the cause-effect relationship is largely speculative, recent data indicate that the position of nuclei should no longer be considered only a means to diagnose muscle disease.